PERANCANGAN SISTEM PEMASARAN BERBASIS WEB PADA SABLON MADEINMAX.CO MENGGUNAKAN METODE WATERFALL - Alnayla Earthza Wilansky; Alifia Jurien Wilansky; Tania Puspita Listya Ningrum; Saprudin (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2024)
Abstract−This research discusses the design and implementation of a web-based ordering information system for Madeinemax.co, a company engaged in providing high-quality screen printing art. The aim of this research is to simplify the ordering and order management process, as well as to improve efficiency andcustomer satisfaction. The research method used is the Waterfall method, which involves stages of analysis, design, implementation, testing, and system maintenance. The results of this research show that the developed information system successfully facilitates the ordering process more effectively, increases thespeed of order processing, and provides accurate information for users. The implementation of this system is expected to support the company's vision and mission in providing superior and inspiring services to the local and global art community.